Pengaruh Penambahan Pasta Daun Pegagan (Centella asiatica L) Terhadap Karakteristik Nugget Ikan Lele (Clarias gariepinus B) - Triarti Sinaga, Yulika; Ekawati, I Gusti Ayu; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This study aims to determine the effect of the addition of Centella leaf paste to the characteristics of catfish nuggets and the right addition of Centella leaf paste that is able to produce nuggets with the best characteristics. The experimental design used Complete Randomized Design (CRD) with the addition of Centella leaf paste consisting of 6 levels: 0%, 20%, 40%, 60%, 80% and 100%. The treatment was repeated 3 times to obtain 18 units of experiment. The data obtained were analyzed by Analysis of Variance, and if the treatment had a significant effect on the observed variables then continued with Duncan Multiple Range Test (DMRT). The results showed that the addition of Centella leaf paste had a very significant effect on the of water content, protein content, antioxidant activity, color (scoring test), had no significant effect on ash content, crude fiber content, aroma (hedonik test), texture (hedonic and skoring), and overall acceptance (hedonic), and also had a significant effect on taste (hedonic) of nugget. Addition of 20% Centella leaf paste had the best characteristics of nugget with content of water 53.05%, ash content 1.89%, protein content 24.35%, coarse fiber content 11.43%, antioxidant activities 237800.42 ppm, the aroma was liked, the color was greenish brown, the texture was rather liked and bit chewy, taste was rather liked, and overall acceptance was rather liked.